CAN BORON AND BORON ISOTOPES BE USED AS A SEDIMENTARY MARKER FOR FIRE EVENTS? A CASE STUDY FROM A HISTORIC URBAN FIRE EVENT IN W FINLAND - Peltola P.; Åström M. (My University, 2006)
The aim of this study was to seek the origin of a B peak found in two sediment profiles from a small lake close to a small-sized town in Finland. The peak was found by chance when an environmental multielement study was performed. Altogether 51 chemical elements were determined with ICP-MS, after aqua regia digestion. None of the other determined elements were enriched or depleted in the B rich layer, including elements derived from sea-salt inclusions (Na and Sr) and anthropogenic sources (Pb, Cu, Cd, Hg, etc.). Boron stable isotopes, dating of the sediment cores, and the B concentrations found in possible source materials suggest that the B rich layer is the result of leaching of wood ash produced in a fire that destroyed half of the nearby wooden town in the early 19th century. The results imply that the concentrations and isotopic signatures of B in lacustrine environments (sediments) can be used to detect historic fires. © 2006 Elsevier Ltd. All rights reserved.